21st Century Critical Thinking Skills Training for Early Childhood Education Teachers Using Computational Thinking Principles - Haryanto, Jessica Febrina (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to guide early childhood education teachers in integrating Computational Thinking (CT) principles into classroom learning using English as the language of instruction. The implementation method of this community service activity consisted of workshops and mentoring sessions. The target participants of this program were PAUD teachers at PPT Mutiara Bunda Ondomohen Surabaya. The data collected through observation sheets and documentation was analyzed to know teachers' ability to incorporate CT principles into teaching and implement them in the classroom. The results of this community service program indicated an improvement in teachers' teaching skills through their efforts to integrate critical thinking skills and CT principles into the learning process.